2006
DOI: 10.1016/j.schres.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cognitive structure in schizophrenia patients and healthy controls using confirmatory factor analysis

Abstract: There is evidence that cognitive task performance breaks down into the same broad domains in schizophrenia as in healthy populations. However, this does not mean that the domains are independent of one another or that the interrelationships among domains are the same between groups. We used confirmatory factor analysis (CFA) to compare the latent structure of a broad neuropsychological battery in schizophrenia patients (n =148) and healthy controls (n =157). Main analyses examined the fit of a hierarchical six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
80
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 37 publications
13
80
0
1
Order By: Relevance
“…Through confirmatory factor analysis and application of gradual restrictions on the model's parameters, the researchers found that the schizophrenia group showed more homogenous cognition than the control group. In our study, although cognitive performance in schizophrenia has been suggested to be fractionated 40,41 , our results corroborate prior studies 42 suggesting that people with schizophrenia have a more unitary cognitive structure. This unitary cognitive performance may be a reflection of the variable cortical and subcortical dysfunction present in schizophrenia 43 or the existence of a more widespread range of test performance among patients than in healthy controls 42 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Through confirmatory factor analysis and application of gradual restrictions on the model's parameters, the researchers found that the schizophrenia group showed more homogenous cognition than the control group. In our study, although cognitive performance in schizophrenia has been suggested to be fractionated 40,41 , our results corroborate prior studies 42 suggesting that people with schizophrenia have a more unitary cognitive structure. This unitary cognitive performance may be a reflection of the variable cortical and subcortical dysfunction present in schizophrenia 43 or the existence of a more widespread range of test performance among patients than in healthy controls 42 .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, although cognitive performance in schizophrenia has been suggested to be fractionated 40,41 , our results corroborate prior studies 42 suggesting that people with schizophrenia have a more unitary cognitive structure. This unitary cognitive performance may be a reflection of the variable cortical and subcortical dysfunction present in schizophrenia 43 or the existence of a more widespread range of test performance among patients than in healthy controls 42 . That's why focus on group average performance, or use of samples with individuals who are at different phases of the illness, may mask the existence of different cognitive profiles amongst patient subgroups 44 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A subsequent study showed that 63.6% of the diagnosis-related variance was attributable to a common factor, with much smaller percentages attributable to performance in other cognitive domains, such as verbal memory (13.8%) and processing speed (9.1%) [33]. The same group demonstrated that, compared to healthy controls, schizophrenia patients showed higher correlations between composite scores of neuropsychological functions in a study of confirmatory factor analysis, consistent with the hypothesis that patients demonstrated a more generalized cognitive ability (or deficit) than controls [34].…”
Section: Development Of a Standardized Cognitive Battery For Schizophsupporting
confidence: 65%
“…In particular, whether performance on all cognitive domains predicts general cognitive function in aggregate or whether generalized cognitive ability hierarchically informs the performance on subdomains of cognition. While some research and expert opinion support a domain model of cognitive deficit in schizophrenia, 7,19,20 recent factor and structural equation analyses from large studies with comprehensive neuropsychological batteries 9,16,[21][22][23] have demonstrated that a single factor of global cognitive function better explains the deficit pattern of schizophrenia (one of these analyses was conducted on the CATIE data set used in this study 16 ). Specifically, these studies have shown that the best fit for the neurocognitive performance data of people with schizophrenia is either a 1-factor model where the factor of global cognitive ability explains the majority of the variance in performance on the specific tests included in the battery without significant input from cognitive subdomains 21,23 or the global factor hierarchically influences performance on the subdomains, which in turn predict performance on the individual tests in the battery.…”
Section: Discussionmentioning
confidence: 92%